PENGARUH BUDAYA KERJA, PEMBERDAYAAN DAN SIKAP KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Rizki Zenia; Nazamuddin .; Dimaswari Sefrizal; Santi Akusti; Sarimin . (Manajemen dan Bisnis, 2021)
Problem of this study how influence of job culture on performance. How influence of    empowerment on performance. How influence of  work attitude on  performance. How influence job culture,  empowerment and  work attitude on   performance. The purpose of this study to determine and analyze the effect of  job culture on   performance. Determine and analyze the effect of   empowerment on   performance. Determine and analyze the effect of  work attitude on   performance. Determine and analyze the effect of  job culture,  empowerment and  work attitude on   performance.  Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job culture variable has a positive and significant effect on performance.  empowerment variable has a positive and significant effect on   performance.  work attitude variable has a positive and significant effect on performance. Job culture,  empowerment and  work attitude variable has a positive and significant effect on   performance.